THE INFLUENCE OF HUMAN RESOURCE POLICIES AND PRACTICES ON JOB PERFORMANCE OF GEN Z MEDIATED BY PERCEIVED ORGANIZATIONAL SUPPORT - Romadhoni, Firmansyah; Nadlifatin, Reny (Jurnal Bisnis dan Keuangan, 2026)
This study investigates the influence of Human Resource (HR) policies and practices on Generation Z’s job performance within the manufacturing sector under significant economic pressure, using Social Exchange Theory (SET) as the guiding framework. A quantitative research design was employed, collecting data from 150 Generation Z workers in Pasuruan Regency's labor-intensive sub-sectors, with data analyzed via Partial Least Squares Structural Equation Modeling (PLS-SEM) and validated through HTMT for discriminant validity, alongside SRMR and Q2 for structural integrity and predictive relevance. The empirical results reveal that while Compensation & Benefits and Equality & Diversity significantly enhance job performance, factors such as Training & Development, Career Development, and Reward & Recognition show no significant effects in this constrained context. Furthermore, Perceived Organizational Support (POS) was confirmed as a critical psychological mediator in these relationships. These findings imply that during economic distress, firms should prioritize basic rights and inclusive environments over long-term development programs to sustain productivity. This study contributes to the SET literature by identifying boundary conditions for the norm of reciprocity and offering unique insights into how non-financial social investments drive performance among Generation Z during economic contraction.